2014
DOI: 10.5194/acp-14-2669-2014
|View full text |Cite
|
Sign up to set email alerts
|

Observations of I<sub>2</sub> at a remote marine site

Abstract: Abstract. Inorganic iodine plays a significant role in the photochemistry of the marine boundary layer, but the sources and cycling of iodine are not well understood. We report the first I 2 observations in marine air that is not impacted by coastal macroalgal emissions or sea ice chemistry. The data clearly demonstrate that the very high I 2 levels previously reported for coastal air are not representative of open ocean conditions. In this study, gas phase I 2 was measured at the Cape Verde Atmospheric Observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 35 publications
(49 reference statements)
7
50
0
Order By: Relevance
“…Additionally, the measured emission rates of iodinated VOCs are unable to explain the observed levels of IO and I 2 Jones et al, 2010b;Großmann et al, 2013;Lawler et al, 2014). Several mechanisms have been introduced to explain the observations and are still under active discussion (e.g.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the measured emission rates of iodinated VOCs are unable to explain the observed levels of IO and I 2 Jones et al, 2010b;Großmann et al, 2013;Lawler et al, 2014). Several mechanisms have been introduced to explain the observations and are still under active discussion (e.g.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Several mechanisms have been introduced to explain the observations and are still under active discussion (e.g. Lawler et al, 2014;Carpenter et al, 2013;MacDonald et al, 2014). Some of these discrepancies may be explained by assuming seasonal or yearly cycles of the iodine sources, but there are also several uncertainties in the iodine chemical mechanism Saiz-Lopez et al, 2012b).…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Very recently the first measurements of I 2 at a remote marine site (Cape Verde) have been reported (Lawler et al, 2014), with night time mixing ratios of up to 1.7 pptv. These mixing ratios are not enough to sustain the levels of IO observed at Cape Verde , which concurs with our laboratory observations of HOI being the major species emitted from the ocean surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have aimed at determining the source gases of iodine and their chemical pathways (see Saiz-Lopez et al, 2012a, and references therein). While emissions of very short-lived (VSL) organic source gases (CH 3 I, CH 2 I 2 , CH 2 ICl and CH 2 IBr) have been observed in supersaturated waters (Carpenter et al, 2012), the existence of an abiotic ocean source of iodine has been directly and indirectly inferred throughout scattered field campaigns and 1-D model works (Read et al, 2008;Jones et al, 2010;Mahajan et al, 2010Mahajan et al, , 2012Gómez Martín et al, 2013;Großman et al, 2013;Lawler et al, 2014). Very recently, laboratory studies have demonstrated the potential of the ocean to emit inorganic hypoiodous acid (HOI) and, to a lesser extent, molecular iodine (I 2 ) following the reaction of ozone with iodide at the sea surface (Carpenter et al, 2013;MacDonald et al, 2014).…”
Section: Introductionmentioning
confidence: 99%